Impact of early heparin therapy on mortality in critically ill patients with sepsis associated acute kidney injury: a retrospective study from the MIMIC-IV database - Zhou, Zhi-Peng; Zhong, Li; Liu, Yan; Yang, Zhen-Jia; Huang, Jia-Jia; Li, Da-Zheng; Chen, Yu-Hua; Luan, Ying-Yi; Yao, Yong-Ming; Wu, Ming (Frontiers in Pharmacology, 2024)
Background Inflammatory-coagulation dysfunction plays an increasingly important role in sepsis associated acute kidney injury(SAKI). This study aimed to investigate whether early heparin therapy improves survival in patients with SAKI. Methods Patients with SAKI were identified from the Medical Information Mart for Intensive Care-IV database. The patients were divided into two groups: those who received heparin subcutaneously within 48 hours after intensive care unit (ICU) admission and the control group, who received no heparin. The primary endpoint was ICU mortality, the secondary outcomes were 7-day, 14-day, 28-day, and hospital mortality. Propensity score matching(PSM), marginal structural Cox model (MSCM), and E-value analyses were performed. Results The study included 5623 individuals with SAKI, 2410 of whom received heparin and 3213 of whom did not. There were significant effects on ICU and 28-day mortality in the overall population with PSM. MSCM further reinforces the efficacy of heparin administration reduces ICU mortality in the general population. Stratification analysis with MSCM showed that heparin administration was associated with decreased ICU mortality at various AKI stages. Heparin use was also associated with reduced 28-day mortality in patients with only female, age >60 years, and AKI stage 3, with HRs of 0.79, 0.77, and 0.60, respectively (P <0.05). E-value analysis suggests robustness to unmeasured confounding. Conclusions: Early heparin therapy for patients with SAKI decreased ICU mortality. Further analysis demonstrated that heparin therapy was associated with reduced 28-day mortality rate in patients only among female, age >60 years and AKI stage 3.